INDONESIAN BANKS RISK-TAKING: THE EFFECT OF LIQUIDITY RISK, CAPITAL BUFFER AND BOPO: Z-SCORE MEASURE ASPPROACH - Yuwonoputro, Dhanesworo Arsojotegto; Syaichu, Muhamad (Faculty of Economics and Business Diponegoro University, 2019)
This study was aimed to examine the effect of liquidity risk, capital buffer and BOPO on banks risk-taking in Indonesia. This study used loan to deposit ratio, non-performing loan, liquidity gap, capital buffer and BOPO as independent variable and banks risk-taking proxied by Z-Score as dependent variable.This study used secondary data retrieved from banking companies’ annual reports listed on Indonesia Stock Exchange Index (IDX) in 2013-2017. Sample used in this study were 110 samples consist of 22 Indonesian banks taken using purposive sampling method. This study used multiple linear regression as analysis method.The results of this study indicate that non-performing loan and BOPO have a positive and significant effect on banks risk-taking. Capital buffer has a negative and significant effect on bank risk-taking, while loan to deposit ratio has a positive and insignificant effect on banks risk-taking and liquidity gap has a negative and insignificant effect on banks risk-taking.